Sipuisilam dalam Selimut Arat Sabulungan Penganut Islam Mentawai di Siberut - Maskota Delfi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
The Mentawai island group, due to relative remoteness, has been able to develop independently from activities on the mainland. Therefore, a large part of the population was raised on the organically developed culture and dynamic capacity of the community. This was possible due to the richly endowed environment, which includes the staple food provision in sago trees and an abundance of wildlife, including boars. The food source became an important element in the traditional believe of Arat Sabulungan, as it served as a binding agent in ritual feasts, bonding of sharing animal protein with clan members, payments to fulfil bride price requirements and traditional fines. In 1954, a compulsory introduction of state sanctioned religions was arranged. As the Mentawains acknowledge certain advanced wisdom and wealth of the sasareu or foreigners, many incentive programs made successful converts. Nevertheless, a remarkable adaptation was included; in which some layers of Mentawai identity was not lost in the conversion. In this adaptation the Islamic faith was infused with local perception.